Persistent Symptoms (Lasting Longer than 1 Year) in Children Hospitalized with Acute COVID-19 Versus Other Conditions - Marta Conde; Irati Gastesi; Lucía de Pablo; Sara Villanueva-Medina; David Aguilera-Alonso; Ana Esteban; Cristina Epalza; María López; Sara Domínguez-Rodríguez; Pablo Gómez; Álvaro Ballesteros; Carlota Pinto; et al. (Children, 2024)
Background: We evaluated the prevalence and characteristics of persistent signs and/or symptoms in children and young people (CYP) one year after hospitalization for acute COVID-19 compared with a control group of CYP hospitalized for other conditions. Methods: We conducted an observational study in three hospitals in Madrid, which included a group of children aged between 1 month and 18 years who were hospitalized due to acute COVID-19 from March 2020 to December 2021. We also selected a comparison group of patients hospitalized for other, unrelated conditions within the same month. Eligible participants had no history of COVID-19 at recruitment or during follow-up. Data were collected from clinical records and a standardized questionnaire completed by the patients’ families. The primary outcome was the presence of persistent symptoms one year after hospitalization. Results: A total of 96 patients were enrolled and analyzed (50 acute COVID-19 patients and 46 non-COVID-19 participants). Of these, 34/96 (35%) met the criteria for persistent symptoms (CYP: 17/50 (34%) COVID-19 participants and 17/46 (37%) non-COVID-19 participants (p = 0.767)). Symptoms persisted ≥12 months in 14/50 (28%) COVID-19 participants and in 7/46 (15%) non-COVID-19 participants (p = 0.140). Both before and after admission, all of the participants provided similar ratings for all of the specific items related to emotional welfare, social relationships, and current activities. Readmissions occurred in 11/50 (22%) COVID-19 participants and in 6/46 (13%) non-COVID-19 participants (p = 0.267). Conclusions: We identified a non-significant difference in the prevalence of persistent symptoms 1 year after hospitalization between children and young people (CYP) with acute COVID-19 and those hospitalized for non-COVID-19-related conditions.